Improved gene therapy for MFRP deficiency-mediated retinal degeneration by knocking down endogenous bicistronic Mfrp and Ctrp5 transcript - Xiao Tian; Qingyun Zheng; Jinyan Xie; Qinlinglan Zhou; Letong Liang; Guotong Xu; Hongyan Chen; Chen Ling; Daru Lu (Molecular Therapy: Nucleic Acids, 2023)
The membrane frizzled-related protein (Mfrp) and C1-tumor necrosis factor related protein 5 (Ctrp5) genes are transcribed as a bicistronic unit and dysregulation of either gene is associated with retinal degeneration in the retinal pigment epithelium (RPE) cells. However, the mechanisms that regulate the expression of the bicistronic transcript remain controversial. Here, we identified a microRNA-based negative feedback loop that helps maintain a normal expression level of the bicistronic Mfrp and Ctrp5 transcript. Specifically, miR-149-3p, a conserved microRNA, binds to the 3′UTR of the Mfrp gene. In MFRP-deficient rd6 mice, the miR-149-3p levels were compromised compared with those in WT mice, resulting in an increase in the bicistronic transcript. We also report a capsid-modified rAAVDJ-3M vector that is capable of robustly and specifically transducing RPE cells following subretinal delivery. Compared with the parental vector, the modified vector elicited similar levels of serum anti-rAAV antibodies, but recruited fewer microglial infiltrations. Most significantly, we also demonstrate that simultaneous overexpressing of MFRP and knockdown of the bicistronic transcript was more effective in rescuing vision than MFRP overexpression alone. Our findings offer new insights into the function of MFRP and provide a promising therapeutic strategy for the treatment of MFRP-associated ocular diseases.